Didymocarpus cordifolius (Gesneriaceae), a new species from southern Yunnan, China - Li, Peng-Wei; Yang, Li-Hua (Phytotaxa, 2022)
Didymocarpus cordifolius, a new species of Gesneriaceae from southern Yunnan Province, China is described and illustrated. The new species is morphologically similar to D. silvarum and D. margaritae, but can be readily distinguished by its short petioles with both glandular and eglandular hairs, pale purple corolla, hairy anthers, and ovary and style of subequal length.